Membangun Karakter melalui Manajemen Pendidikan - Sukatin Sukatin; Rizqi Anggunani; Auliya Sofffy Fikriyani; Juwita Anjelina Putri; Kifayatul Atqiya; Evi Mardianti; Abizar Alghifari; Zulham Halman (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Character education has become a fundamental aspect of educational development because it aims to develop students who possess moral values, responsibility, discipline, and positive attitudes. Achieving this objective requires effective educational management that systematically integrates character values into all school activities. This study aims to examine the role of educational management in developing students’ character through planning, implementation, evaluation, strategic management, and the collaboration of educational stakeholders. The research employed a library research method by collecting and analyzing data from books, scientific journals, and other relevant academic sources. The findings indicate that educational management plays a strategic role in strengthening character education through well-planned programs, effective implementation, continuous evaluation, and comprehensive management strategies integrated into the curriculum, school culture, and extracurricular activities. The success of character development is also influenced by the active involvement of principals, teachers, parents, and the school community. However, challenges related to human resources, facilities, administration, and institutional readiness remain obstacles to effective implementation. The study implies that strengthening educational management and fostering sustainable collaboration among all stakeholders are essential to creating a supportive educational environment that promotes students’ character development and contributes to achieving national education goals.